Mucosal Schwann cell hamartomas do occur the gastric mucosa - report of two cases mimicking fundic gland polyps - Márcia Helena Oliveira Castro; Rodrigo Jose Felipe; Amanda Fernandes Cardoso; Carlos Leonardo Martins Guimarães; Paulo Roberto Fontes Athanazio; Daniel Abensur Athanazio (BMC, 2019)
Abstract Mucosal Schwann cell hamartomas (MSCHs) are recently characterized benign spindle cell lesions of the colon and rectum. There is only one report of MSCHs in the stomach (antrum). Herein, we present the first reports of MSCHs occurring in the fundic mucosa as lesions that endoscopically mimicked a typical fundic gland polyp. Case 1. A 56-year-old woman sought medical attention due to epigastric pain. A small polypoid lesion in the fundic mucosa was removed with an endoscopic impression of a fundic gland polyp. Case 2. A 66-year-old man sought medical attention due to epigastric pain. The patient underwent antral and corporal biopsies that showed mild non-active gastritis without Helicobacter pylori infection. Small polypoid lesions in the fundic mucosa were seen; one was removed with an endoscopic impression of the fundic gland polyp. At the microscope, both lesions were entirely intramucosal, ill-defined spindle cell aggregations, suggesting a fascicular growth pattern. Both lesions were strongly and diffusely positive for S100. Awareness of this lesion is relevant to avoid the diagnosis of other benign spindle cell lesions that are associated with familial syndromes.